Wording the World : Veena Das and Scenes of Inheritance (Book collections on Project MUSE., 2015)
"The essays in this book examine how important themes in Veena Das's work have been critically assimilated in the work of a younger generation. Looking at the relation between the event and the everyday, the essays ask how we might trace the picture of thinking in anthropology through ethnography and through artistic, literary and philosophical practice"--